2020
DOI: 10.3389/fmicb.2020.01581
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an MRT-qPCR Assay for Detecting Coinfection of Six Vertically Transmitted or Immunosuppressive Avian Viruses

Abstract: Marek's disease virus (MDV), reticuloendotheliosis virus (REV), avian reovirus (ARV), chicken infectious anemia virus (CIAV), infectious bursal disease virus (IBDV), and fowl adenovirus (FAdV) are important causes of disease in poultry. To investigate the infection status of the above six viruses in chickens in China, 1,187 samples from chicken flocks were collected and tested using a newly developed multiplex reverse-transcription quantitative real-time PCR (MRT-qPCR) assay in the study. A series of validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…The obtained DNA was used to quantify the viral load by RT-qPCR. Primers were designed based on conserved regions of the FAdV genome using Primer Premier 5.0 (N-F: 5′AAAACTGAGACTTTCCCACAA 3′; N-R: 5′AGATACCCTCCGAAGAACTAC 3′), as described by Li et al [ 17 ]. All samples were tested in triplicate, and assays were repeated at least twice.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained DNA was used to quantify the viral load by RT-qPCR. Primers were designed based on conserved regions of the FAdV genome using Primer Premier 5.0 (N-F: 5′AAAACTGAGACTTTCCCACAA 3′; N-R: 5′AGATACCCTCCGAAGAACTAC 3′), as described by Li et al [ 17 ]. All samples were tested in triplicate, and assays were repeated at least twice.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, co-infection of four immunosuppressive pathogens including CIAV has been detected in Shandong Province ( 17 , 18 ). Recently, 1,187 clinical samples from major poultry farms nationwide from 2017 to 2020, have been tested for co-infection with six immunosuppressive pathogens including CIAV ( 19 ). These surveys have confirmed the widespread nature of CIAV in China, which has seriously affected the development of the poultry industry.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, further PCR detection showed that all 11 HEV positive samples were mixed infections, of which the infection rates of HEV and CIAV, HEV and FAdV were highest. CIAV is an important immunosuppressive virus in chicken, and according to the epidemiology investigation of co-infection of vertically transmitted or immunosuppressive viruses in chickens by Li et al, CIAV had the highest detection ratio [15]. FAdV has been prevalent in poultry in recent years and caused huge economic losses to poultry industry in China [16,17].…”
Section: Discussionmentioning
confidence: 99%